Rapid Assessments of Leatherback Small-Scale Fishery Bycatch in Internesting Areas in the Eastern Pacific Ocean - Ortiz-Alvarez, Clara; Pajuelo, Mariela; Grados, Daniel; Abrego, Marino E.; Rebeca Barragán-Rocha, Ana; Barrantes, Mariano; Cotto Sánchez, Alejandro; Fonseca, Luis G.; Gadea Espinal, Velkiss; Mangel, Jeffrey C.; Rguez-Baron, Juan M.; Santidrian-Tomillo, Pilar; et al. (Frontiers in Marine Science, 2020)
The East Pacific (EP) leatherback population is listed by the IUCN Red List of Threatened Species as Critically Endangered. Despite conservation efforts, mainly focused on nesting beaches, its population has declined by over 90% since the 1980s. A major current threat is fisheries bycatch, which has been primarily documented in small-scale gillnets and longlines within South American migration and foraging habitats, but scarcely reported in fisheries that operate in areas near nesting beaches (i.e., inter-nesting areas). To assess the impact of small-scale fisheries on EP leatherbacks inhabiting waters north of the equator we conducted rapid bycatch assessments interviews in five countries (Mexico, Nicaragua, Costa Rica, Panama and Colombia), some of which host the main EP leatherback nesting beaches and inter-nesting areas. A total of 1778 interviews were conducted across 79 fishing ports (Mexico = 37, Nicaragua = 6, Costa Rica = 5, Panama = 17 and Colombia = 14). Leatherback bycatch was reported in all countries, and in 54% of ports assessed by 7% (n = 125) of fishers interviewed. Interviews enabled identification of inter-nesting areas where leatherback bycatch was higher and periods during which fisheries interaction events were more frequent. Bycatch events were most frequently reported in gillnets and secondarily in longlines. Data were extrapolated across fishing fleets to estimate that 345 ± 210 (mean ± SD) individual leatherbacks are caught annually in the ports assessed. Our study provides a first evaluation of leatherback bycatch by small-scale fisheries in countries of the eastern Pacific Ocean where leatherbacks nest, and it highlights areas close to index nesting beaches where conservation efforts targeting bycatch reduction and bycatch mortality may be focused.